2013
DOI: 10.1371/journal.pone.0082388
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Is a Negative Regulator of Osteoblast Mineralization

Abstract: An excessive intake of vitamin A has been associated with an increased risk of fractures in humans. In animals, a high vitamin A intake leads to a reduction of long bone diameter and spontaneous fractures. Studies in rodents indicate that the bone thinning is due to increased periosteal bone resorption and reduced radial growth. Whether the latter is a consequence of direct effects on bone or indirect effects on appetite and general growth is unknown. In this study we therefore used pair-feeding and dynamic hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
78
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 61 publications
13
78
0
Order By: Relevance
“…Importantly, however, non-decalcified histology revealed that this dietary induction of hypervitaminosis A did not impair bone matrix mineralization, but caused specific alterations in bone cell differentiation, as the number of osteoclasts per bone surface was significantly increased by the high-retinol diet, while the number of osteoblasts was decreased. These data are in full agreement with a recently performed study where the authors supplemented the diet with even higher concentrations of retinol and observed a negative impact on the bone formation rate [48]. We next addressed the question of whether retinoic acid would directly affect gene expression in primary osteoblasts.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Importantly, however, non-decalcified histology revealed that this dietary induction of hypervitaminosis A did not impair bone matrix mineralization, but caused specific alterations in bone cell differentiation, as the number of osteoclasts per bone surface was significantly increased by the high-retinol diet, while the number of osteoblasts was decreased. These data are in full agreement with a recently performed study where the authors supplemented the diet with even higher concentrations of retinol and observed a negative impact on the bone formation rate [48]. We next addressed the question of whether retinoic acid would directly affect gene expression in primary osteoblasts.…”
Section: Discussionsupporting
confidence: 88%
“…Collectively, our findings raise the possibility that the influence of retinoids on osteoblastogenesis and bone remodeling are attributable to a few specific changes in gene expression, and that the previously reported long-term effects on osteoblast proliferation and expression of differentiation markers have to be considered as secondary events [5,7,[9][10][11][12][13]48].…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Retinoic acid (RA) has been shown to play multiple roles in bone development and repair by exerting pleiotropic effects on cells of the chondroblast, osteoblast and osteoclast lineages (Adams et al, 2007;Allen et al, 2002;Conaway et al, 2013;Dranse et al, 2011;Koyama et al, 1999;Laue et al, 2008Laue et al, , 2011Li et al, 2010;Lie and Moren, 2012;Lind et al, 2013;Nallamshetty et al, 2013;Song et al, 2005;Spoorendonk et al, 2008;Weston et al, 2003;Williams et al, 2009). Although partially conflicting results were reported, the general consensus for osteoblastogenesis is that RA signaling restricts osteoblast differentiation but promotes subsequent bone matrix synthesis by mature osteoblasts.…”
Section: Introductionmentioning
confidence: 99%